UPAYA KEPALA MADRASAH DALAM MENINGKATKAN KUALITAS TENAGA PENDIDIK DI MA RAUDHATUL HUDA AL-ISLAMY SIDOMULYO - Mulyani, Mulyani (UNISAN JURNAL, 2023)
Teachers are important learning agents in their position in the course of an educational process. The good and bad of education depends on how a teacher manifests and applies his contributions to both formal and non-formal institutions. The purpose of this study is to determine the efforts of the head of the madrasa in improving the quality of educators at MA Raudhatul Huda Al-Islamy Sidomulyo. This research uses qualitative descriptive research methods. Data collection techniques in the form of observations, interviews, and documentation. Data analysis includes data collection, data presentation, and drawing conclusions. The results of the study show that the quality of human resources (HR) at MA Raudhatul Huda Al Islamy Sidomulyo Kec. Negrikaton Kab.Pesawaran can be said to be quite good, but it still needs to continue to be developed and improved. This is because the discipline of teachers and employees is still lacking, in terms of the division of subjects in this school, there are still many teachers who hold subjects that are not in accordance with their respective fields. In terms of discipline in carrying out their teaching duties, teachers have used the syllabus and learning plan and have followed educational developments well, especially regarding learning problems. Efforts to improve the quality of human resources (HR) include including upgrading, seminars and training of teachers, participating in deliberation activities and teacher meetings in similar fields of study.